Gender, the work-life course, and livelihood strategies in a South Indian fish market - Holly M. Hapke and Devan Ayyankeril (Gender, Place and Culture Vol. 11, No. 2, June 2004, 2004)
This article examines how gender ideologies differentially inform men and women's work-life courses in the fishing economy of southern India. Drawing on interviews conducted with fish traders in Trivandrum, India in 1993-94 and 1999, we construct economic life histories for men and women traders. These are then used to illustrate how gender creates different patterns of paid work for men and women throughout their life courses and to analyze how men and women formulate livelihood strategies differently as a result.